Pattern and associated socio demographic factors of tobacco use among health care staff in a tertiary care setting at Faridabad - Prasad, Nidhi; Kumar, Binay (International Journal Of Community Medicine And Public Health, 2020)
Background: This study aimed at assessing prevailing pattern and risk factors of tobacco consumption among health care workers of tertiary care centre, in Faridabad. Methods: A cross-sectional approach was used. A sample of 306 participants included housekeeping and nursing orderly. Participants were interviewed during their lunch time. Semi structured questionnaire was used for data collection. Results: The overall prevalence of tobacco use was found to be 42.8% (n=306), of which (30.7%) prevalence among housekeeping’s compared to nursing orderlies (12.7%). The consumption of smokeless tobacco was higher among housekeeping staff. Khaini (45%) was the main consumption type, followed by hookah (21%) and cigarettes (19.5%) among the current tobacco user (n=133). The consumption of tobacco was found to be associated with gender (male), education, and nature of job (designation) at the hospital setting. Conclusions: Tobacco use is very common in hospital staff in Faridabad as reflected by results of our study. We should build on success encountered in banning smoking in educational institutions and healthcare facilities. This is important for their health and also overall health of patients also as they can influence the behaviour of people that surrounds them.